2023
DOI: 10.1186/s40164-023-00402-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of potential resistance mechanisms and therapeutic targets for the relapse of BCMA CAR-T therapy in relapsed/refractory multiple myeloma through single-cell sequencing

Abstract: Background BCMA CAR-T is highly effective for relapsed/refractory multiple myeloma(R/R-MM) and significantly improves the survival of patients. However, the short remission time and high relapse rate of MM patients treated with BCMA CAR-T remain bottlenecks that limit long-term survival. The immune microenvironment of the bone marrow (BM) in R/R-MM may be responsible for this. The present study aims to present an in-depth analysis of resistant mechanisms and to explore potential novel therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 96 publications
0
5
0
Order By: Relevance
“…Although loss of BCMA has been described, 15 , 16 , 17 the majority of patients with relapsed disease after BCMA-directed CAR-T continue to have positive BCMA expression on MM cells, and other factors including CAR-T persistence, T-cell exhaustion, anti-CAR Abs, and the tumor microenvironment may be important determinants of disease relapse. 18 , 19 , 20 Given that BCMA expression is still present in the majority of relapses, 18 retreatment with BCMA-targeted therapies may be a feasible strategy after BCMA-directed CAR-T relapse. In the MajesTEC-1 trial, an ORR of 45% was observed for teclistamab in patients who had prior BCMA-directed CAR-T, with the observed baseline BCMA expression on relapse after CAR-T being comparable with that observed in patients naïve to BCMA treatment on the trial.…”
Section: Discussionmentioning
confidence: 99%
“…Although loss of BCMA has been described, 15 , 16 , 17 the majority of patients with relapsed disease after BCMA-directed CAR-T continue to have positive BCMA expression on MM cells, and other factors including CAR-T persistence, T-cell exhaustion, anti-CAR Abs, and the tumor microenvironment may be important determinants of disease relapse. 18 , 19 , 20 Given that BCMA expression is still present in the majority of relapses, 18 retreatment with BCMA-targeted therapies may be a feasible strategy after BCMA-directed CAR-T relapse. In the MajesTEC-1 trial, an ORR of 45% was observed for teclistamab in patients who had prior BCMA-directed CAR-T, with the observed baseline BCMA expression on relapse after CAR-T being comparable with that observed in patients naïve to BCMA treatment on the trial.…”
Section: Discussionmentioning
confidence: 99%
“…In the scRNA-seq analysis, we first utilized the hg38 reference genome and employed the default parameters of Cell Ranger v.7.1.0 software for gene alignment ( 18 ). Following this, we conducted standard single-cell RNA sequencing data analysis using the ‘Seurat’ package in R. After filtering out cells with mitochondrial gene percentage (pMT) over 20%, hemoglobin gene percentage (pHB) over 1%, and those expressing fewer than 500 genes, while retaining genes expressed in at least five cells, we successfully obtained 91,810 high-quality cell samples.…”
Section: Methodsmentioning
confidence: 99%
“…This treatment has also been effective in CD24 subclone-bearing tumors, suggesting that targeting pancreatic cancer stem cells with this method could be a feasible therapeutic strategy for pancreatic cancer. Bispecific BCMA-CD24 CAR-T cells have shown almost complete tumor clearance ability against multiple myeloma cells in vitro and in vivo ( 80 ). However, the antibody used by CD24 CAR-T cells was mouse scFv SWA11, which may cause allergic reactions.…”
Section: Targeting Cd24 For Cancer Immunotherapymentioning
confidence: 99%